Habilidades socioemocionais como ferramenta para o trabalho social: avaliação de uma metodologia de capacitação para profissionais do Sistema Único de Assistência Social - Camara, Marcela de Silva e Sá Bittencourt (2020)
In this dissertation, I have elaborated a qualitative evaluation of a training methodology for members staff of the Unified System of Social Assistance (Sistema Único de Assistência Social; SUAS). The Casa das Caldeiras Project its concept is based on Social-Emotional skills to create the best environment to connect people, as a result, facilitate the practice, implementation, and development of those abilities. As an arm of Associação Cultural Casa das Caldeiras (ACCC) the project has a major influence over the cultural creative process and responsibilities to keep preserved the memories, with the territory and organize meetings. Through CONDECA's [2015] funding program, the Casa das Caldeiras Project, has neared to Social Assistance and as the answer to their requirements and their questions, consequently, was created the Immersive Training Course for Unified System of Social Assistance (Capacitação Imersiva para Profissionais do SUAS). I’ve adopted a constructionist understanding and an approach about a theoretical-methodology with focusing the discursive practices of daily life created and elaborated at the Nucleus of Studies in Discursive Practice's (Núcleo de Práticas Discursivas no Cotidiano: Direitos, Riscos e Saúde - NUPRAD/PUC-SP).Through a review of the discussion circle within the attendees during the Immersive Training Course, I have investigated the relation, of SUAS member's staff whether or not had settled between professional practices and the content presented from the Casa das Caldeiras Project. Meantime, I’ve implemented as an analysis method of information, the dialogues charts. The charts present the enlightenment of dialogue procedures, subsequently, the possibilities to identify the direction that the researcher chosen to have the conclusions presented and guarantee the research accuracy. Was used the democratic evaluation conception to base about methods choice and the analysis of information. I have debated the conceptual structure of Casa das Caldeiras Project, specifying the Socio-Emotional skills and the differentiating from Big Five theory also introducing “the Elements” features that compose and structure the Project’s methodology. I have done an SUAS brief presentation from your formation as public policy, the fighting against welfare programs unto the normalization, the importance of graduation in Social Assistance, willing improvements with an Immersive Training Course. I have described the history and characteristics of the Immersive Training Course, afterwards, I have presented within the analysis, the voice of members staff who’s had participated in the encounter. Were analyzed five discursive categories: environment, members staff, professional practices, socioaid policy and the evaluation of the Immersive Training Course. The discursive analysis had supported the assessment of the Immersive Training Course in three stages: The Immersive Training Course’ experience, the acquirement of the “Elements” and probably parallels between the “Elements” and labor practices. The evaluation suggests that the Immersive Training Course of the Casas das Caldeiras Project attendees were able to establish the parallels between the “Elements” and the labor practice enhancing the social work with the Families